Internal memory data protecting problems of the Renesas microcontrollers - Kondrashov, K.K.; Levina, A.B. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
The problem of protecting the information contained in the internal memory of the Renesas RL78 Family Microcontrollers is considered. The vulnerability of these microcontrollers has been identified and in vestigated, which allows extracting data from the built-in flash memory using a programmer. A method of automated recovery of the contents of the entire memory area, based on specially developed software, has been tested. The results of the study indicate the insufficient effectiveness of the access restriction measures implemented by the manufacturer. A variant of changing the programmer’s control command, leading to an increase in data security, is described. A technique for complete recovery of flash memory data is presented, tested in a program developed in the LabVIEW environment.